Analisis Dampak Transformasi Digital Terhadap Peran Sumber Daya Manusia Di Koperasi Mahasiswa Unm - Kurniawan, Agung Widhi (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2025)
Digital transformation has become a key factor in changing the way organizations operate, including at the Student Cooperative of Universitas Negeri Makassar (UNM). This study aims to analyze the impact of digital transformation on the role of human resources (HR) within the student cooperative. The findings indicate that the implementation of digital technology enhances operational efficiency, facilitates access to information, and strengthens communication among members. Additionally, digital transformation encourages the development of digital skills among members, which is essential for navigating challenges in the modern era. The role of HR in the cooperative is becoming increasingly strategic, with members not only contributing to operational activities but also engaging in innovation and business development. By leveraging technology, the Student Cooperative of UNM is able to adapt to the needs of its members and improve its competitiveness in an increasingly competitive market. This research provides valuable insights for cooperative managers on how to utilize digital transformation to achieve organizational goals and enhance member welfare.